2010
DOI: 10.3109/13645700903492969
|View full text |Cite
|
Sign up to set email alerts
|

Skill accreditation system for laparoscopic gastroenterologic surgeons in Japan

Abstract: The Japan Society for Endoscopic Surgery (JSES) has established an Endoscopic Surgical Skill Qualification System and started examination in 2004. Non-edited videotapes were assessed by two judges in a double-blinded fashion with strict criteria. Two kinds of criteria, namely common and procedure-specific, were prepared. The common criteria were designed to evaluate set-ups, autonomy of the operator, display of the surgical field, recognition of surgical anatomy, co-operation of the surgical team. The procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 5 publications
2
107
0
Order By: Relevance
“…Celecoxib is a selective COX-2 inhibitor that is rapidly absorbed, possesses good oral bioavailability, and has a short mean plasma half-life. The analgesic effect of celecoxib has been demonstrated in 16 both orthopedic and obstetric surgery [26][27][28][29]. Our findings indicate that all patients tolerated 4 days of celecoxib, and as a result, celecoxib provided stable pain relief following LG without any severe adverse effects in the liver, kidney, gastrointestinal tract, or hemocytes.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Celecoxib is a selective COX-2 inhibitor that is rapidly absorbed, possesses good oral bioavailability, and has a short mean plasma half-life. The analgesic effect of celecoxib has been demonstrated in 16 both orthopedic and obstetric surgery [26][27][28][29]. Our findings indicate that all patients tolerated 4 days of celecoxib, and as a result, celecoxib provided stable pain relief following LG without any severe adverse effects in the liver, kidney, gastrointestinal tract, or hemocytes.…”
Section: Discussionsupporting
confidence: 52%
“…This was a bi-center study, in which a total of eight surgeons performed LG. However, the same surgeon, who is qualified by the Japanese endoscopic surgical skill qualification system [16] and whose experience includes more than 500 laparoscopic gastric resections, was associated with all operations as either an operator or instructive assistant. From January 2011 to postoperatively.…”
Section: Patientsmentioning
confidence: 99%
“…The surgeon in charge of the team had acquired a specialist qualification from the Japan Society of Coloproctology23, which recognized his years of clinical experience in approved facilities and successful completion of the specialist qualifying examination24. Laparoscopic operations were performed by a surgeon who was similarly accredited by the Japanese Society for Endoscopic Surgery25. All operations were performed according to the standard procedure described in the seventh edition of the Japanese General Rules for Clinical and Pathological Studies on Cancer of the Colon, Rectum and Anus22.…”
Section: Methodsmentioning
confidence: 99%
“…For quality control in this study, surgeons operating on patients in the laparoscopic arm had to be certified by the Endoscopic Surgical Skill Qualification System. This accreditation system for gastrointestinal surgery was established in 2004, and the surgical skill assessment system has contributed to the standardization of the laparoscopic technique and has enhanced the surgical skills of laparoscopic surgeons in Japan (8,9). In addition, a central review of the surgical procedure was carried out on the basis of photographs taken after lymph node dissection for all patients and video footage for arbitrarily selected patients (29).…”
Section: Current Studies Of Ladg For Advanced Gastric Cancer (Agc)mentioning
confidence: 99%
“…For the purpose of improving the laparoscopic technique, the Japan Society for Endoscopic Surgery (JSES) established the Committee for the Endoscopic Surgical Skill Qualification System in 2001 (8,9). With regard to the clinical relevance of this examination, Mori et al demonstrated that surgical complications were significantly fewer in those who passed the examination compared with those who failed (8).…”
Section: Introductionmentioning
confidence: 99%